ACUTE PROMYELOCYTIC LEUKEMIA - Wati, Ni Wayan Kurnia; Ariawati, Ketut (Medicina, 2015)
Acute promyelocytic leukemia (APL) is a subtype of acute myeloid leukemia (AML). The disease isvery uncommon in children less than 10 years of age. Every sign and symptom that present on patientwith APL are caused by the infiltration of the bone marrow with leukemic cells and resulting failure ofnormal hematopoiesis. Without the normal hematopoietic elements, the patient is at risk for developinglife-threatening complications of anemia, infection due to neutropenia, and hemorrhage due tothrombocytopenia, disseminated intravascular coagulation, fibrinolysis, and proteolysis of maturecells. We reported one case of a nine-year-old girl with pale, limp, recurred fever, hematome, andpetechiae. Physical examination revealed pale in conjunctiva, ginggival hypertrophy, and hepatomegaly.Complete blood count showed normochromic normocytic anemia, thrombocytopenia, and leukopenia,with neutropenia. Bone marrow aspiration revealed a bundle of auer rod, promyelocyte 60 %, myeloblast2 %, concluded AML(M3). We provided chemoterapy with vitamine A, daunorubicine, and cytarabine,but the condition was decreased and finally died after the first cycle of chemotherapy. [MEDICINA2015;46:178-83].Leukemia promielositik akut (LPA) merupakan salah satu subtipe dari leukemia mielositik akut(LMA). Penyakit ini sangat jarang pada anak-anak kurang dari 10 tahun. Semua tanda dan gejalaklinis pada pasien dengan LPA disebabkan karena infiltrasi sumsum tulang oleh sel-sel leukemiadan mengakibatkan kegagalan hematopoiesis normal. Komplikasi LPA yang mengancam jiwa antaralain anemia, infeksi akibat netropenia, dan perdarahan akibat trombositopenia, disseminatedintravascular coagulation, fibrinolisis, dan proteolisis. Kami melaporkan satu kasus anak sembilantahun dengan keluhan pucat, lemas, demam berulang, hematoma, dan petekie. Pada pemeriksaanfisis didapatkan konjungtiva pucat, hipertrofi gingiva, dan hepatomegali. Pemeriksaan darah lengkapmenunjukkan anemia normokronik normositik, trombositopenia, dan leukopenia, dengan neutropenia.Aspirasi sumsum tulang menunjukkan adanya bundle of auer rod, promyelocyte 60%, myeloblast 2%,disimpulkan sebagai AML (M3). Kami kemoterapi dengan vitamin A, daunorubisin, dan sitarabin,tapi kondisi anak kemudian menurun dan akhirnya meninggal setelah periode pertama kemoterapi.[MEDICINA 2015;46:178-83].